2023
DOI: 10.1002/kjm2.12679
|View full text |Cite
|
Sign up to set email alerts
|

Robotic arm use for upper limb rehabilitation after stroke: A systematic review and meta‐analysis

Abstract: Several studies have reported the effects of robotic arms on improving upper limb function in patients with stroke. However, previous studies have reported inconsistent findings that may lead to incorrect applications of robotic arm use. Six databases were searched for relevant randomized controlled trials. Meta-analyses were performed for upper limb performance measures, including subgroup analysis of pooled upper limb rehabilitation data such as stroke stage and intervention delivery dose.Furthermore, the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…This combination enhances patient enjoyment [19] and the provision of real-time performance feedback that allows therapists to adapt the training to the patient's individual needs [20]. When compared to dose-matched conventional therapy, some studies point to improved outcomes with robotic interventions [17,21,22], while a large body of research indicates that robotic therapy is currently non-inferior to conventional interventions [15,[23][24][25][26].…”
Section: Robotic Devices Have Become Increasingly Popular In Neuroreh...mentioning
confidence: 99%
“…This combination enhances patient enjoyment [19] and the provision of real-time performance feedback that allows therapists to adapt the training to the patient's individual needs [20]. When compared to dose-matched conventional therapy, some studies point to improved outcomes with robotic interventions [17,21,22], while a large body of research indicates that robotic therapy is currently non-inferior to conventional interventions [15,[23][24][25][26].…”
Section: Robotic Devices Have Become Increasingly Popular In Neuroreh...mentioning
confidence: 99%
“…A previous study reported that higher-intensity robotic therapy exercises improved upper-extremity impairment after stroke [ 9 ]. However, the effectiveness of robotic therapy has focused on the distal hand and fingers, and no significant efficacy of robotic therapy for hemiplegic shoulders has been elucidated [ 10 ]. In particular, it is difficult to safely assist shoulder elevation against gravity (vertical movement) through robotic intervention because of the complex musculoskeletal anatomy of the shoulder.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific studies have shown that continuous passive rehabilitation exercise therapy can effectively prevent muscle atrophy, promote the remodeling of nervous system motor function, 3–9 prevent tendon adhesion and joint stiffness, and improve blood circulation and joint rehabilitation effects at the exercise site, to achieve the treatment of finger. 10 , 11 Finger rehabilitation machinery has become a key research direction of international rehabilitation engineering and robotics, and patients can carry out efficient autonomous rehabilitation training by wearing manipulators. 12–14 …”
Section: Introductionmentioning
confidence: 99%